Paciente masculino de 70 años de edad con enfermedad pulmonar obstructiva crónica. - Sánchez Guerrero, Yomira Estefanía (2020)
Through this research work we present the acronyms with their meanings, signs, symptoms and recommendations of the disease studied. The importance of knowing COPD, Chronic Obstructive Pulmonary Diseases, how to treat it if we are in advanced stages and how to recognize the stages in which the disease is found. Chronic obstructive pulmonary disease (COPD) is a progressive, life-threatening lung disease that can cause dyspnea (initially associated with exertion) and predisposes to exacerbations and serious illness. The main cause of COPD is exposure to tobacco smoke (active and passive smokers). COPD is an incurable disease, but treatment can relieve symptoms, improve quality of life, and reduce the risk of death.